PENERAPAN MODEL LEARNING CYCLE (LC) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS Va SDN 163 PEKANBARU - Simanjuntak, Novita Sari Simanjuntak Sari Simanjuntak; Alpusari, Mahmud Alpusari; ', Syahrilfudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem inthis studyis the lack of science students learning outcomes, it is seen from the average value is 66.73 students. Of the 41 students who achieve as core above KKM is only 13 students (31.7%), while students who have no treached the KKM as many as 28 students (66,73%), the KKM set is 73 based on these problems is necessary to study aclass action by applying the learning cycle model. This study aimstoimprove learning outcomes VA grade science studentsof SDN163 Pekanbaru school the number of students is 41 people consistingof 20 male students and 21 female students.The percentage of completeness students learning outcomes in basic scoreis from31,7% with an average of 66.73 increased to70,7% with an average 72,29 in the first cycle, and the second cycle in creased to 82.9 with an average of 78.24, and the third cycle increased to 90.2% with an average of 84,58. Percentage of teacher activity also increased, as seen from the percentage of all teachers in the first cycle of 67.5% increased to 82.4% in the second cycle, and increased again in the third cycle is 92.5%. The percentage of student activity also increased from 62.5% in the first cycle increased to77.5% in the second cycle and increased again to 92.5% in the third cycle. From the above explanation can be seen that through the application of model learning cycle, can improve learning outcomes VA grade science students of SDN 163 Pekanbaru. Key words: Application of Model Learning Cycle (LC), Science Learning Outcomes